(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Sovereignty is one of the main elements in the establishment of a country. Sovereignty should be the full right of a state without restrictions and without intervention from other groups or countries outside the country. Globalization that brings the world into one unit inevitably makes world countries become integrated with each other. Globalization has brought various policies that have led to the introduction of free markets. The enactment contains certain provisions and standards that must be implemented by each country that is a party to the agreement. This reduces the state’s ability to be sovereign because there are restrictions and interventions from various groups in setting economic rules. This study aims to analyse the limitations of a country’s economic sovereignty with the existence of free trade. The method used in this study is descriptive qualitative. The data used is secondary data sourced from the literature review. Data collection is carried out by literature observation. The results showed that the existence of free trade reduces state sovereignty due to restrictions and interventions in forming economic regulations in the country of these. Indonesia as one of the participating countries in free trade, also reaps the impact of limited sovereignty because the formation of economic regulations must refer to provisions and agreement agreements in a free market.